ANALISIS TINGKAT PEMAHAMAN AKUNTANSI BERBASIS AKRUAL DALAM PENYUSUNAN LAPORAN KEUANGAN PEMERINTAH DAERAH : PADA KANTOR CAMAT TANJUNG BATU KAB. OGAN ILIR - Febransyah Febransyah; Dinda Astari (Universitas Tridinanti, 2021)
In reforms in the field of state finance, a significant change is a change in government accounting that is transparent and accountable. One of the important keys in the management of state finances is related which aims to provide basic guidelines in the preparation and presentation of government financial reports, both central and local governments. Government Accounting Standards (SAP) are requirements that have legal force in an effort to improve the quality of government financial reports in Indonesia. This study aims to determine the readiness of the TanjungBatu sub-district office in implementing accrual-based Government Accounting Standards in preparing financial reports.The data source used in this study is primary data. Primary data is data obtained by the author directly from parties related to the Financial Statements of the TanjungBatu District Head Office. In addition, secondary data is also used in the form of financial reports. Data collection techniques were carried out by observation and in-depth interviews with the head of the financial subdivision and expenditure treasurer at the TanjungBatu sub-district office, OganIlir Regency and the research data used were primary data, namely data obtained directly from respondents in the form of interview data and documentation. The data analysis technique used is qualitative analysis which is expressed in the form of words, sentences and images that are collected and analyzed.The results of this study indicate that the level of understanding in the implementation of accrual-based government accounting standards is a reflection of a formality is quite good. This is supported by a government regulation that requires all local governments including the OganIlir Regency Government, especially the TanjungBatu Sub-District Office to implement accrual-based SAP. Suggestions from the author are needed for the development of understanding of government managers, especially employees of the TanjungBatu sub-district office on accrual-based Government Accounting Standards. Keywords: Government Accounting Standards, Accrual Basis, Financial Statements.